Implementasi Supervisi Akademik Kepala Sekolah dalam Peningkatan Profesionalisme Guru di SMK Katolik Kota Samarinda - Lorensius, Lorensius; Hanim, Zaenab; Warman, Warman (CV. Creative Tugu Pena, 2022)
The purpose of this study was to determine the principal's academic supervision in increasing teacher professionalism. This research uses a qualitative approach. Data collection techniques through observation, interviews, and documentation. The subjects of this study were principals, vice principals, and teachers. The results showed that the implementation of academic supervision by the principal was based on the need to overcome the problems of learning devices, lesson plans, learning materials, classroom management, assessment of learning outcomes, teacher discipline, and implementation of character education. In order for supervision to be carried out effectively, the principal seeks to build good relationships with teachers by fostering a sense of kinship, communicating with each other and providing information, providing motivation, and being an example for teachers. The supervision activities carried out are: 1) the supervisor and the teacher enter the classroom; 2) the teacher explains to the students the purpose of the supervisor's arrival; 3) the supervisor observes the teacher's appearance by using the observation assessment format that has been made and agreed upon; 4) during the observation the supervisor focuses on the contract agreement with the teacher. Keywords: Supervisi Akademik, Profesionalisme Guru, Implementasi Supervisi Akademik